COMPARATIVE AND STRUCTURAL ANALYSIS OF COMMERCIAL TERMS IN UZBEK AND ENGLISH - Abdullayeva Feruza Suyunovna; Karimboeva Surayyo Alibek qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: The article endeavors to explore the cultural, economic, and pragmatic underpinnings that inform the use of commercial terms in Uzbek and English, recognizing the broader sociolinguistic and communicative contexts in which these terms are employed.